METHOD'S REALIZATION PRINCIPLES OF INFORMATION PROTECTION MANAGEMENT SYSTEM AUDITING AT TELECOMMUNICATION COMPANIES - V. A. Boiprav; L. L. Utin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The evaluation of the activity specifics of Belarus telecommunication companies is made. The realization principles of information protection systems auditing method in these companies is grounded with use of the evaluation results and the requirements of Belarus normative and legal documents in the spheres of information security and telecommunication.